Indigenous knowledge of medicinal plants among Dao and Muong ethnic minority groups in Ba Vi National Park, Hanoi - Sam, Hoang Van (Academia Journal of Biology, 2012)
This paper presents a survey the medicinal plants and their traditional use by Muong and Dao ethnic minority groups in Ba Vi National park, Vietnam. A total of 257 medicinal plant species belonging to 204 genera and 81 families are used by Dao and Muong people in Ba Vi National Park. These species are used for treatment of 63 different diseases. Of them, the Dao ethnic group used 144 species, the Muong ethnic group used 30 species, and 83 species were used by both ethnic minority groups. Women in Ba Vi National Park are mainly responsible for the health care of their household, so they have better knowledge of medicinal plants than men and are also mainly engaged in collecting medicinal plants. The Dao ethnic group has better knowledge and experience of medicinal plants than the Muong, and they use much more species for diseases treatment compared with the Muong people in the research area. Knowledge about using medicinal plants to treat disease is also a difference. 83 species have similar medicinal uses among the two groups, while there are 11 species having at least one medical use the same among the Muong and Dao, although one of the groups may also use it for other treatments. An additional 23 medicinal plant species are used by both the Muong and Dao, but there are no similarities in the medicinal uses.